The Role of Gender Moderates the Effect of Entrepreneurial Mindsets on Student Intention - Bela, Lena Ria; Riani, Asri Laksmi; Indriayu, Mientasih (Dinamika Pendidikan, 2021)
The purpose of this research was to explain how gender roles in moderating the entrepreneurial mindset affect one's intentions. Is it through the entrepreneurial mindset that a man will be able to increase his intentions or is it greater than women? The method used in this article was Moderating Regression Analysis (MRA) and Process macro Hayes version 3.5.3. This study had a population of 5170 students and 371 students were used as samples. The results of the analysis indicated if the entrepreneurial mindset had a positive and significant effect on intentions. There was no effect of gender moderation on the effect of entrepreneurial mindset and intention. An entrepreneur needs to own an entrepreneurial mindset in him to cultivate intentions. This improvement can be done by designing and creating a program that can develop and grow the entrepreneurial mindset of students without the need to pay attention to gender-related characteristics (both men and women have the same opportunities). The uniqueness of this research was to test the effect of an entrepreneurial mindset on intention, moderated by gender. The contribution to this research was the effect of gender moderating the effect of entrepreneurial mindset on student intentions.